2021
DOI: 10.1002/oby.23082
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate and Bisphenol Urinary Concentrations, Body Fat Measures, and Cardiovascular Risk Factors in Dutch School‐Age Children

Abstract: Objective: The purpose of this study was to investigate the associations of urinary phthalates and bisphenols at age 6 years old with body fat and cardiovascular risk factors at 6 and 10 years and with the change from 6 to 10 years. Methods: Among 471 Dutch children, the phthalates and bisphenols urinary concentrations at 6 years and BMI, fat mass index, android fat mass, blood pressure, glucose, insulin, and lipids blood concentrations at 6 and 10 years were measured. Results: An interquartile range increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
(94 reference statements)
0
27
0
Order By: Relevance
“…In our study, we did not find a significant relationship between the tBPA levels and blood pressure profiles. Similarly, a study conducted with 471 Dutch children aged 6–10 years reported that there was no significant relationship between blood pressure and BPA after multiple testing corrections [ 27 ]. However, in a study conducted with 132 children aged 6–18 years in Iran, the urinary BPA concentrations of the participants were found to be 282.53 ± 166.02 μg/g-cre and a linear increase in blood pressure was reported among the tertiles determined according to the BPA concentration [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we did not find a significant relationship between the tBPA levels and blood pressure profiles. Similarly, a study conducted with 471 Dutch children aged 6–10 years reported that there was no significant relationship between blood pressure and BPA after multiple testing corrections [ 27 ]. However, in a study conducted with 132 children aged 6–18 years in Iran, the urinary BPA concentrations of the participants were found to be 282.53 ± 166.02 μg/g-cre and a linear increase in blood pressure was reported among the tertiles determined according to the BPA concentration [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to BPA being one of the endocrine disruptors, studies are showing its hepatotoxic, immunotoxic, obesity-forming, and carcinogenic effects [ 19 , 23 ]. The results of the few studies conducted in the pediatric age group on the relationship of BPA with cardiovascular diseases are inconsistent [ 24 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…15 In contrast, the Generation R cohort study in the Netherlands found that BPS concentrations at age 6 years were inversely associated with BMI at age 10 years. 22…”
Section: Discussionmentioning
confidence: 99%
“…15 In contrast, the Generation R cohort study in the Netherlands found that BPS concentrations at age 6 years were inversely associated with BMI at age 10 years. 22 The difference in the direction and magnitude of associations of BPA and BPS with adiposity could be owing to differences in the biological pathways they affect. For instance, BPS may have more specific effects on adipogenesis and lipid accumulation than BPA through differentially expressed genes in preadipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation